Wrestling with the Posthuman: Understanding the Relationship between Human Autonomy and Technology - Malík, Jaroslav (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
In this paper, I examine the term "posthuman," which is often used to describe the possible future state of humanity. However, it is often difficult to understand what this term is meant to describe. I examine the claims of two movements that use this term: transhumanism and posthumanism. These movements are presented in the context of humanism. Both movements present how technologies are changing human autonomy and how posthuman beings arise out of this change. I formalise and critique these accounts of the posthuman. I conclude that neither movement adequately explains the transition from the human to the posthuman.